Assessment of Load Carrying Capacity of a Typical SGDHR Pipe Bend after Subject to Severe Seismic Loading. (2015) - Kumar, R. Suresh; Selvaraj, P.
Abstract: Because of the stringent safety criteria evolved after the Fukushima accident, it is necessary to ensure the availability of the Safety Graded Decay Heat Removal (SGDHR) system even under Beyond Design Basis Event (BDBE). Towards ensuring the availability of the SGDHR system for the decay heat removal, the structural integrity of the SGDHR piping system has been demonstrated under BDBE by testing. Accordingly one of the typical full scale SGDHR pipe bend have been tested towards the assessment of the seismic margin available in the design of PFBR SGDHR piping system. Maximum load carrying capacity of this pipe bend was demonstrated as 2.9 times of the maximum potential EQ possible at the PFBR site with a return period of once in 10 6 years without any loss of structural integrity. This test results ensures the availability of the SGDHR piping system even under BDBE for the decay heat removal without getting any compromise on the loss of structural integrity of the piping system. Numerical analysis also carried out to understand the overall stress distribution and also to compare the experimental results. It indicated that, the crown experiences highest tensile stress and intrados portion under compressive stress upon typical in-plane bending moment. The comparison of the numerical analysis and the experimental result for the collapse behaviour matches perfectly within the elastic portion. Slight deviation observed in the plastic region may be due to ther eason that, the material property taken for the numerical analysis was based on the uni-axial data. But the experimental results are multi axial in nature. The small difference could have been improved by applying the multi axial material property data for the numerical prediction. In the present analysis numerical results over predicts the plastic deformation.